The International Court of Justice and the Macedonian –Greek Case - Ahmedi, Bujar; Ahmeti, Besian (European Journal of Multidisciplinary Studies, 2018)
In the international law there is often a mention of the peaceful arrangements of international disputes. The resolution of international disputes is also part of the most important principles of international law. Given the historical development of international law, we observe that states that have been subjected to the fictitious subjects of international law have often had disputes between them on interrelated issues. For these differences between states to be provided international law different mechanisms are being considered in order to resolve disputes and diplomatic aids and in some cases also judicial means that serve to resolve these disputes. This paper presents the dispute between Macedonia and Greece regarding the issue of the name where the role of the international community has been extremely important by putting its diplomacy at its disposal with the sole aim of reaching a resolution of the parties’.